The role of civil society in social transformation: the case of Ukraine - Florez Cubillos, Ligia Andrea (Universidad Francisco de Paula Santander, 2015)
The revolutions that have taken place in Eastern Europe and the beginning of the century were a first element considered to identify the potential of social movements in the transformation of the realities of the states in different latitudes and the importance of globalization in this type of manifestations. However, the achievements of civil society in this scenario have been overshadowed by theresurgence of conflicts. In this sense, this article studies the particular case of Ukraine and then raises  how the orange revolution was a milestone in the awakening to democracy of a communist state but that the claim of civil society lacked structural elements that allowed the consolidation of an economic, political and social model adjusted to its own conditions